2017
DOI: 10.3389/fcell.2017.00092
|View full text |Cite
|
Sign up to set email alerts
|

Details Matter: Noise and Model Structure Set the Relationship between Cell Size and Cell Cycle Timing

Abstract: Organisms across all domains of life regulate the size of their cells. However, the means by which this is done is poorly understood. We study two abstracted “molecular” models for size regulation: inhibitor dilution and initiator accumulation. We apply the models to two settings: bacteria like Escherichia coli, that grow fully before they set a division plane and divide into two equally sized cells, and cells that form a bud early in the cell division cycle, confine new growth to that bud, and divide at the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…A range of different hypotheses for how cell size could regulate this genetic network have been proposed. We highlight two paradigms of size control: inhibitor dilution or activator accumulation (37,38). Recent observations support an inhibitor dilution model enacted through Whi5, wherein the growth-mediated dilution of Whi5 relative to a roughly constant concentration of Cln3 during G1 increases the rate of passage through Start as cells grow larger (12,39).…”
Section: Introductionmentioning
confidence: 71%
“…A range of different hypotheses for how cell size could regulate this genetic network have been proposed. We highlight two paradigms of size control: inhibitor dilution or activator accumulation (37,38). Recent observations support an inhibitor dilution model enacted through Whi5, wherein the growth-mediated dilution of Whi5 relative to a roughly constant concentration of Cln3 during G1 increases the rate of passage through Start as cells grow larger (12,39).…”
Section: Introductionmentioning
confidence: 71%
“…Analysis and simulations of the initiation-centric model of Eqs. [34][35] show that it produces emergent adder correlations at division [13,40], as long as the magnitude of the fluctuations in the coordination between initiation and division is much less than that in the control of initiation (σ t σ T ). This is indeed the case in experiments for fast-growing bacteria, although the picture appears different for slow-growing bacteria [21], which we discuss later.…”
Section: Molecular Mechanisms To Implement Cell Size Regulationmentioning
confidence: 97%
“…While experiments have suggested that the upstream control occurs over initiation of DNA replication rather than cell division in various microorganisms [6,9,25,39], we first review a simpler model where the accumulation of initiators triggers cell division. The model leads to the adder correlations observed in several species of bacteria and other microorganisms [13,20,40].…”
Section: Molecular Mechanisms To Implement Cell Size Regulationmentioning
confidence: 99%
“…We here employ the first method. We assume that individual cells grow exponentially [16] over a well-defined period T g . Additional variability in cell cycle length can be achieved by introducing an additional refractory phase with exponentially distributed waiting times and the average waiting time T r , which we set to T r = 0 in this work.…”
Section: F Cell Proliferation and Mitosismentioning
confidence: 99%